Unloading in Refractory Cardiogenic Shock After Out-Of-Hospital Cardiac Arrest Due to Acute Myocardial Infarction—A Propensity Score-Matched Analysis - Sieweke, Jan-Thorben; Akin, Muharrem; Beheshty, Julian-Arman; Flierl, Ulrike; Bauersachs, Johann; Schäfer, Andreas (Frontiers in Cardiovascular Medicine, 2021)
Aims: Unclear neurological outcome often precludes severely compromised patients after out-of-hospital cardiac arrest (OHCA) from mechanical circulatory support (MCS), while it may be considered as rescue therapy for patients with refractory cardiogenic shock (rCS) in the absence of OHCA. This analysis sought to investigate the role of left ventricular (LV) unloading in patients with rCS related to acute myocardial infarction (AMI) after OHCA. Methods: Of 273 consecutive patients receiving microaxial pumps in the Hannover Cardiac Unloading Registry between January 2013 and August 2018, 47 presented with AMI–rCS following successful resuscitation. Subsequently, the patients were compared by propensity score matching to patients with OHCA AMI–rCS without MCS. The patient data for OHCA without LV unloading was available from 280 patients of the Hannover Cooling Registry for the same time period. Furthermore, the patients with OHCA without rCS were compared to the patients with OHCA AMI–rCS and LV unloading. Results: In total, 15 OHCA AMI–rCS patients without MCS were matched to patients with AMI–rCS and Impella. Patients without LV support had a higher proportion of a cardiac cause of death (n = 7 vs. n = 3; p = 0.024). LV unloading with Impella counteract rCS status and was associated with a preferable 30-day survival (66.7 vs. 20%, p = 0.01) and a favorable neurological outcome after 30 days (Cerebral Performance Category ≤2, 47 vs. 27%). Impella support is associated with a higher 30-day survival (odds ratio, 2.67; 95% confidence interval, 1.02–13.66). Conclusion: In patients after OHCA with AMI–rCS, Impella support incorporated in a strict standardized treatment algorithm results in a preferable 30-day survival and counteracts severe rCS status.